Evaluation of microwave heating on fluid invasion and phase trapping in tight gas reservoirs - Wang, H.; Rezaee, M. Reza; Saeedi, A. (2015)
During well drilling, completion, stimulation and fracturing, moisture invasion and phase trapping lead to a drastic permeability reduction, which prevent the tight gas reservoir producing at an economical rate. To eliminate such formation damage, the power of microwave was considered. As an effective heating technique, the application of microwave heating in removing moisture in the near wellbore area is relatively novel and thus lack of experience. This paper simulates effects of microwave heating on the formation damage and gas production rate of a tight gas reservoir in Western Australia and demonstrates its effectiveness. The well information for a tight gas well in Western Australia was obtained to simulate the actual gas production in numerical model. Finite Element Analysis (FEA) software and industry standard reservoir simulation software were coupled to simulate microwave heating at borehole scale. The electrical conductivity was extracted from well logs and the dielectric constant and loss factor of the reservoir rock was calculated using the empirical equations and proven mixing law. Two cases studied are in non-fractured well and fractured well. In each study, same water amounts were injected for 5days followed by a same period of clean-up and gas production, the difference is one model has microwave heater while the other not. The effects of microwave heating on water saturation and relative permeability to gas were made between two scenarios of gas production with heating and without heating. The electric filed and magnetic field distributions and the heat generation rate in the near wellbore area were calculated based on the actual petrophysical properties of the reservoir rock and Maxwell's Equations. Based on the results from FEA, the heat generated by microwave was applied on the well models respectively. After microwave heating started, gas relative permeability increased and water saturation decreased through the heated zone. In all the cases, microwave heating seems to be an effective way to remove moisture and to recover the gas productivity back to a high rate. But in non-fractured reservoir, the gas production rate has achieved the most improvement. The present paper focuses on the interaction of microwave and trapped moisture in the reservoir. By simulating the heating assisted gas production, illustrate how microwave heating was able to increase gas well productivity by reducing water saturation. More factors need to be considered in the future, and the suggestions have been given in this paper.